A novel mutation of Beta-ketothiolase deficiency: The first report from Iran and review of literature - Vakili, Rahim; Hashemian, Somayyeh (Iranian Journal of Child Neurology, 2018)
Background: Beta-ketothiolase deficiency is a rare autosomal recessive disorder characterized by an inborn error of isoleucine catabolism and affecting ketone body metabolism. Clinical features characterized by intermittent keto acidotic episodes associated with clinical signs and symptoms of toxic encephalopathy such as lethargy, hypotonia, vomiting, tachypnea, and coma in some patients, with an onset during infancy or toddler-hood. Case presentation: A two months old girl presented with acute episode of fever and toxic encephalopathy with attack of vomiting, hypotonia, lethargy, tonic clonic seizures and then a day in coma, few days after vaccination .After then similar episodes happened until 7 months age. . Biochemical tests that suggested diagnose of beta ketothiolase deficiency were attacks of ketoacidosis with urinary exertion of 2-methyl-3-hydroxybutric acid 2-methyl aceto acetic acid tiglylglycine. In genetic assessment we detected a novel homozygous mutation c.664A> C (p. Ser 222 Arg) in ACAT gene. This is a first report of beta ketothiolase deficiency confirmed by molecular analysis from Iran. Conclusion: we report on a homozygous variant in the ACAT1 gene that is the first time we detect this variant and is a novel mutation. According to the obtained result and patient’s phenotype, we recommended carrier testing for all informative family members to recognize mutations in asymptomatic family members.